1996
DOI: 10.1021/jp952231b
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Y+, Zr+, Nb+, and Mo+ with H2, HD, and D2

Abstract: Guided ion beam mass spectrometry is used to examine the kinetic energy dependence of reactions of the second row transition metal cations, Y + , Zr + , Nb + , and Mo + , with molecular hydrogen and its isotopologues. By using a meter long flow tube ion source, we are able to create Zr + , Nb + , and Mo + ions that are believed to be in their electronic ground state terms and primarily in the lowest spin-orbit levels and Y + mostly in its ground state. Corresponding state-specific reaction cross sections are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 34 publications
6
109
1
Order By: Relevance
“…A direct comparison of the thresholds from reaction 4 and 5 in Table 1 suggests that D 0 (Th + −CH 3 ) is 0.27 ± 0.22 eV larger than D 0 (Th + −H) and that D 0 (Th + −CD 3 ) is 0.12 ± 0.14 eV larger than D 0 (Th + −D), with a weighted average (after ZPE corrections) of 0.15 ± 0.12 eV. This is comparable to results for the transition metal congeners, Zr +15, 53 and Hf + , 25,69 where MCH 3 + and MH + BDEs are similar in strength, and to Ti + , 88 where the BDE for TiCH 3 + is stronger than that for TiH + by 0.2 ± 0.2 eV. Similar to the results for ThH + , theory overbinds by 0.4−0.9 eV, again, in part because of spin−orbit effects discussed below.…”
Section: Inorganic Chemistrysupporting
confidence: 73%
See 1 more Smart Citation
“…A direct comparison of the thresholds from reaction 4 and 5 in Table 1 suggests that D 0 (Th + −CH 3 ) is 0.27 ± 0.22 eV larger than D 0 (Th + −H) and that D 0 (Th + −CD 3 ) is 0.12 ± 0.14 eV larger than D 0 (Th + −D), with a weighted average (after ZPE corrections) of 0.15 ± 0.12 eV. This is comparable to results for the transition metal congeners, Zr +15, 53 and Hf + , 25,69 where MCH 3 + and MH + BDEs are similar in strength, and to Ti + , 88 where the BDE for TiCH 3 + is stronger than that for TiH + by 0.2 ± 0.2 eV. Similar to the results for ThH + , theory overbinds by 0.4−0.9 eV, again, in part because of spin−orbit effects discussed below.…”
Section: Inorganic Chemistrysupporting
confidence: 73%
“…22,23,25,27,28,30,53,69,70,86 In all cases, the difference is attributed to competition with the formation of the metal carbene because of a shared, common intermediate. Because reactions of M + with H 2 produce only one product, no competition exists that may delay the onset of reaction.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…The ions then undergo ∼10 5 collisions with He and ∼10 4 collisions with Ar in the meter-long flow tube before entering the guided ion beam apparatus. Results obtained previously 21 indicate that the Mo + ions produced in the DC/FT source are exclusively in their a 6 S ground state (less than 0.1% excited states). 47,48 and experimental work 49 has shown that endothermic cross sections can be modeled using eq 1 where σ 0 is an energy-independent scaling parameter, E is the relative translational energy of the reactants, E el is the average electronic energy of the reactants (0 in the present case), E 0 is the reaction threshold at 0 K, and n is a parameter that controls the shape of the cross section.…”
Section: Introductionmentioning
confidence: 82%
“…Generally, these conditions have been found to thermalize the ions, thereby producing atomic ions in their ground electronic state. For example, on the basis of comparisons to a surface ionization source, the DC/FT source was found to generate Sc + [34], Fe + [35], Co + [36], Ni + [37], Ru + [38], Rh + [38], and Pd + [38] ions with an average electronic temperature of 700 ± 400 K, and Y + , Zr + , Nb + , and Mo + ions with an average electronic temperature of 300 ± 100 K [39]. The populations of Ir + ions created under such conditions have been discussed in a previous paper [57], and rely on energies taken from spectroscopic work of Van Kleef and Metsch [40].…”
Section: Ion Sourcementioning
confidence: 99%